Carcinogenesis of renal cell carcinoma reflected in HLA ligands: A novel approach for synergistic peptide vaccination design. (2nd August 2016) - Klatt, Martin G.; Kowalewski, Daniel J.; Schuster, Heiko; Di Marco, Moreno; Hennenlotter, Jörg; Stenzl, Arnulf; Rammensee, Hans-Georg; Stevanović, Stefan
ABSTRACT: Despite recent advances in immunotherapy of renal cell carcinoma (RCC), peptide vaccination strategies still lack an approach for personalized peptide vaccination that takes intra- and inter-tumoral heterogeneity and biological characteristics into account. In this study, we use an immunoprecipitation and mass spectrometry-based approach supplemented by network analysis of HLA ligands to target this goal. By analyzing HLA-presented peptides for HLA class I and II of 11 malignant and 6 non-malignant kidney tissue samples, more than 2, 700 peptides and 1, 600 corresponding source proteins were identified. A high overlap with HLA ligands derived from peripheral blood mononuclear cells (PBMCs) was detected most likely due to tumor-infiltrating inflammatory cells and therefore excluded from network analysis. Subsequent biological function analysis of HLA ligands by the GeneMANIA online platform showed enrichment for well established, but also novel, pathways and biological processes involved in carcinogenesis of RCC almost exclusively in malignant tissue samples. By exploring source proteins involved in these overrepresented pathways, we verified various known tumor-associated antigens (TAAs) for RCC (e.g., CA9, EGLN3, IGFBP3, MMP7, PAX2, VEGFA, or EGFR) but could also detect novel TAAs for RCC (e.g., PLOD2, LOX, ENPEP, or TGFBI). Some of these new TAAs had already been shown to elicit a T cell response in cancer patients. Thus, network analysis of HLA ligands provided a new platform for implementing personalized, multipeptide vaccines with potentially synergistic antitumor effects.